The effect of ultrasonication on calcium carbonate crystallization in the presence of biopolymer - Kirboga, Semra; Oner, Mualla; Akyol, Emel (ELSEVIER, 2014)
Synthesis of calcium carbonate (CaCO3) was carried out using sonication in aqueous solution medium. The effect of the probe immersion depth (MD) and the amplitude of sonicator on calcium carbonate crystallization were studied in the absence and presence of biopolymer, carboxymethyl inulin (OW). Calcium carbonate crystals synthesized with and without ultrasound were compared. X-ray diffraction (XRD) analysis showed that calcium carbonate obtained in the presence of biopolymer was a mixture of calcite and vaterite whereas there was only calcite polymorph in the absence of biopolymer. In the presence of biopolymer, the relative fraction of vaterite increased with the application of sonication process. The higher amplitude resulted in the higher relative vaterite fraction. The results showed that the probe immersion depth and the amplitude affected the morphology of calcium carbonate. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Calcium carbonate; Crystallization; PRECIPITATION; GROWTH; POLYELECTROLYTES; CACO3; Crystallography; Materials Science; Physics